2022
DOI: 10.3390/microorganisms10030555
|View full text |Cite
|
Sign up to set email alerts
|

Variable Legionella Response to Building Occupancy Patterns and Precautionary Flushing

Abstract: When stay-at-home orders were issued to slow the spread of COVID-19, building occupancy (and water demand) was drastically decreased in many buildings. There was concern that widespread low water demand may cause unprecedented Legionella occurrence and Legionnaires’ disease incidence. In lieu of evidenced-based guidance, many people flushed their water systems as a preventative measure, using highly variable practices. Here, we present field-scale research from a building before, during, and after periods of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 44 publications
6
30
0
Order By: Relevance
“…However, they are consistent with values measured in cold and hot water at taps after varying lengths of stagnation in buildings located in the same water distribution system than the sports complex sampled in the present study (Bédard et al, 2018;Dias et al, 2019). Observations from this study also appear consistent, yet with slightly higher values of total cell counts, than those measured after a 7-week shutdown in Swiss research buildings during the COVID-19 pandemic (Rhoads et al, 2022). Mean values for the proportion of intact cells (Figure 1D) were in agreement with prior observations of first draw samples in chlorinated water containing 15-41% of viable cells after 24 h to 10 days of distal water stagnation (Bédard et al, 2018).…”
Section: Elevated Bacterial Indicators Loads Are Observed After Long ...supporting
confidence: 90%
See 2 more Smart Citations
“…However, they are consistent with values measured in cold and hot water at taps after varying lengths of stagnation in buildings located in the same water distribution system than the sports complex sampled in the present study (Bédard et al, 2018;Dias et al, 2019). Observations from this study also appear consistent, yet with slightly higher values of total cell counts, than those measured after a 7-week shutdown in Swiss research buildings during the COVID-19 pandemic (Rhoads et al, 2022). Mean values for the proportion of intact cells (Figure 1D) were in agreement with prior observations of first draw samples in chlorinated water containing 15-41% of viable cells after 24 h to 10 days of distal water stagnation (Bédard et al, 2018).…”
Section: Elevated Bacterial Indicators Loads Are Observed After Long ...supporting
confidence: 90%
“…The high positivity rates of L. pneumophila by culture-based method and qPCR results (Table 1) recovered in first draw and flushed samples indicate a broad and systemic contamination of the building hot and tempered water systems. Whereas some studies carried out during the pandemic reported either no detectable L. pneumophila (Hozalski et al, 2020) or low positivity and concentrations of L. pneumophila (Dowdell et al, 2022, submitted to Environmental Science and Technology), others measured quantifiable concentrations in similar ranges as those observed in this study for samples representative of points of use (10 1 -10 4 MPN/L or CFU/L; Giglio et al, 2020;Rhoads et al, 2022).…”
Section: Widespread Occurrence Of L Pneumophila In Showerheadssupporting
confidence: 59%
See 1 more Smart Citation
“…Building CH-1 also reported significant heat losses in the primary recirculating line and passive recirculation on individual floor loops, leading to suboptimal temperatures for control of L. pneumophila . 52…”
Section: Resultsmentioning
confidence: 99%
“…Site-specific investigations were conducted at several of the sampling locations, the results of which are or will be reported elsewhere. 52,53 This study presents a cross-sectional analysis of potential L. pneumophila exposure risks in buildings with diverse uses, plumbing configurations, operation, and climate regions.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%